(untitled) (VERITAS LEGIS JOURNAL, 2026)
In this article, the author examines topical issues regarding the transformation of the penitentiary system of the Republic of Kazakhstan amidst large-scale advancements in science and technology. The author explores the concept of the progressive system of punishments as a key component of the mechanism for humanizing criminal policy and reducing the «prison population». Special attention is paid to the application of modern scientific and technological achievements—specifically in the fields of Artificial Intelligence (AI) and IT technologies—within the process of executing punishments, implementing educational measures, and conducting probation control. The author emphasizes that achieving a sufficient level of public safety is impossible without the widespread use of modern tools for monitoring and supervising the behavior of individuals within the criminal justice system. The main objective of the study is to develop theoretical principles and practical recommendations for improving the progressive system through the implementation of digital solutions. To achieve this, the author defines the concept of the progressive system, examines international experience in electronic monitoring (such as GPS and VR therapy), and justifies the need to transfer probation control functions to specialized services. The article analyzes global practices, including the use of biometric bracelets in the USA, emotion recognition systems in China, and coding courses in the UK. In conclusion, the author highlights a comprehensive approach that combines traditional correctional measures with advanced control methods and AI supervision in rehabilitative efforts. The implementation of these proposed measures aims to reduce recidivism rates.